Analisis Penyebab Kenaikan Temperatur Air Tawar pada Sistem Pendingin Mesin Induk di HT Kresna 3116 - Syavessandro Marchio Sangkastria Diadema; Sugeng Marsudi; Maxima Ari Saktiono (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
This study aims to analyze the factors causing the increase in fresh water cooling temperature in the Main Engine, the impacts on engine performance, and the corrective actions taken to overcome Cooling System problems on board Harbour Tug (HT) Kresna 3116. The research was conducted during the sea practice period (PRALA) from October 5, 2024, to October 5, 2025, using a descriptive qualitative research method. Data were collected through direct observation in the engine room, interviews with the Chief Engineer and engine crew, documentation, and analysis of Cooling System operational data. The results showed that the increase in fresh water cooling temperature from the normal condition of 70°C to 85°C was caused by several factors, including blockage of the Sea Chest due to mud and marine debris, scale accumulation in the fresh water cooler, damage to the Mechanical Seal of the Fresh Water Pump, and the less-than optimal implementation of the Planned Maintenance System (PMS). These problems reduced the effectiveness of the heat transfer process, causing the exhaust gas temperature to increase up to 460°C, decreasing combustion efficiency, increasing fuel consumption, and potentially leading to Overheating of the Main Engine. To address these issues, several corrective actions were implemented, including cleaning the Sea Chest and fresh water cooler, replacing the damaged Mechanical Seal on the Fresh Water Pump, renewing the Coolant, and carrying out PMS activities regularly and continuously. After these corrective measures were taken, the fresh water cooling temperature returned to its normal range of approximately 70°C, and the system pressure returned to 2.5 bar. Based on the research findings, it can be concluded that regular maintenance and monitoring of the Cooling System are essential to maintain Main Engine performance, improve vessel operational reliability, and prevent disruptions that could hinder sailing operations.